How large are housing and financial wealth effects? A new approach - Christopher D. Carroll; Misuzu Otsuka; Jiri Slacalek (European Central Bank (ECB), 2010)
This paper presents a simple new method for measuring `wealth effects' on aggregate consumption. The method exploits the stickiness of consumption growth (sometimes interpreted as reflecting consumption `habits') to distinguish between immediate and eventual wealth effects. In U.S. data, we estimate that the immediate (next-quarter) marginal propensity to consume from a change in housing wealth is about 2 cents, with a final eventual effect around 9 cents, substantially larger than the effect of shocks to financial wealth. We argue that our method is preferable to cointegration-based approaches, because neither theory nor evidence supports faith in the existence of a stable cointegrating vector.
Keywords: E21; E32; C22; 330; asset prices; Consumption Dynamics; housing wealth; wealth effect; Privater Konsum; Vermögenseffekt; Wohneigentum; Kapitalanlage; Theorie; USA